2011
DOI: 10.1093/annonc/mdq391
|View full text |Cite
|
Sign up to set email alerts
|

First-line erlotinib and bevacizumab in patients with locally advanced and/or metastatic non-small-cell lung cancer: a phase II study including molecular imaging

Abstract: First-line treatment with bevacizumab and erlotinib in stage IIIb/IV NSCLC resulted in an NPR of 75%. OS was however disappointing. Early response evaluation with FDG-PET is the best predictive test for PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 41 publications
0
34
1
1
Order By: Relevance
“…The primary endpoint of the study was the disease control rate (DCR), defined as the rate of subjects with no progression (based on RECIST 1.0) after 6 weeks of treatment (12)(13)(14). To be able to discontinue the trial early if the treatment showed insufficient activity, a 2-stage design was implemented (Simon optimal design; p0…”
Section: Statisticsmentioning
confidence: 99%
“…The primary endpoint of the study was the disease control rate (DCR), defined as the rate of subjects with no progression (based on RECIST 1.0) after 6 weeks of treatment (12)(13)(14). To be able to discontinue the trial early if the treatment showed insufficient activity, a 2-stage design was implemented (Simon optimal design; p0…”
Section: Statisticsmentioning
confidence: 99%
“…Previous studies have shown that NPR, used as a study endpoint, can predict clinical benefit in cancer patients. [13][14][15] When designing this study, we presumed that the NPR could be improved from 64% in the PC group to 84% after 12 wk (almost 4 cycles) of PC-G treatment. Our results showed that the intercalated addition of gefitinib did not improve the treatment outcomes not only with regard to NPR but also with regard to ORR, PFS, or OS.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, administering bevacizumab and erlotinib together may have additional clinical benefits because bevacizumab and erlotinib act on two different pathways. Combination of bevacizumab and erlotinib was well tolerated in clinical trials but did not improve OS (Table 3) [50][51][52][53]. The recent phase III trial ATLAS, assessing bevacizumab and erlotinib met its primary endpoint with a significant (28%) decrease in the risk of progression and an increase in the median PFS of 1.1 months comparing with erlotinib alone [54].…”
Section: Targeted Therapymentioning
confidence: 99%